PERAN PENGETAHUAN AKUNTANSI DAN KEPRIBADIAN WIRAUSAHA DALAM PENGAMBILAN KEPUTUSAN INVESTASI - Nurani Putri Ayulansae; Priyastiwi Priyastiwi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
Accounting information is information needed by an entrepreneur to make investment decisions. A good entrepreneurial personality will make someone want to continue to develop the business they already have, one way to develop an existing business is to invest. The recording of financial transactions is very important for the profit to be achieved for business continuity so that the business does not stop in the middle of the road. However, currently many entrepreneurs do not have good accounting knowledge, so many entrepreneurs do not record transactions in their businesses so that no financial information is generated to make investment decisions. This study aims to determine the existence of a positive and significant relationship between accounting knowledge and entrepreneurial personality on the use of accounting information in making investment decisions. The data analysis technique used is multiple linear regression analysis technique. The results of this study indicate that accounting knowledge and entrepreneurial personality have a positive and significant effect on the use of accounting information in making investment decisions.